The Effect of Economic Growth, Education, and Urbanization on Population Migration in Makassar City - Angrayani A; Andi Jam’an; Asri Jaya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to determine of Economic Growth, Education, and Urbanization influence Population Migration in Makassar City. The type of research used is quantitative research using secondary data obtained from time series data from 2014 - 2023. Data was collected and analyzed using multiple linear regression analysis with SPSS (Statistical Product and Service Solutions) version 24 to identify whether there is an effect between Economic Growth, Education, and Urbanization on Population Migration in the City of Makassar. The results of this study indicate that (1) Economic Growth Variable (X1) has a negative and insignificant effect on Population Migration in Makassar City. This is evidenced by the coefficient value of multiple linear regression analysis of 0.339 with a significant value greater than 0.05 or (0.243> 0.05). Also evidenced by the t-count value which is smaller than the t table value, namely (1.293 < 1.943). (2) The Education Variable (X2) has a negative and insignificant effect on Population Migration in Makassar City. This is evidenced by the coefficient value of multiple linear regression analysis of 0.205 with a significant value greater than 0.05 or (0.508> 0.05). Also evidenced by the t-count value which is smaller than the t table value, namely (0.704 < 1.943). (3) Urbanization variable (X3) has a negative and insignificant effect on Population Migration in Makassar City. This is evidenced by the coefficient value of multiple linear regression analysis of -0.478 with a significant value greater than 0.05 or (0.855 > 0.05). Also evidenced by the t-value which is smaller than the t-table value, namely (-0.191 < 1.943).